Improvement the Vehicle Suspension System Performance Using Fuzzy Controller - Hanafi, Dirman (International Journal of Integrated Engineering, 2020)
An ideal car suspension system should be stiff enough for better handling while soft enough for better ride comfort factor to the passenger. Passive suspension system often have fixed shock absorber which compromise in between ride comfort and handling factors. In this paper, an active suspension system of a quarter car based on fuzzy control is developed to meet both need of ride comfort and good road handling. The suspension is assumed consist of spring and variable shock absorber. Fuzzy controller has function to control the variable shock absorber. The control structures are based on the combination of the body displacement, wheel displacement and suspension. The proposed controller system has been simulated, and is then compared with the response of passive suspension. Simulation results show that fuzzy controller based suspension system provide better ride comfort and road handling, because it decreases the vehicle body acceleration, small overshoot and settling time.